Short Communication: New records of Graphis (Graphidaceae, Ascomycota) in Bali Island, Indonesia - JUNITA HARDINI; RINA SRI KASIAMDARI; SANTOSA SANTOSA; PURNOMO PURNOMO (Society for Indonesian Biodiversity, 2018)
Hardini J, Kasiamdari RS, Santosa, Purnomo. 2018. Short Communication: New records of Graphis (Graphidaceae, Ascomycota) in Bali Island, Indonesia. Biodiversitas 19: 112-118. Graphis is a genus of the lichen family Graphidaceae, which is found living attached to Plumeria spp. trees as its substrate. The purpose of this study was to determine the species diversity of Graphis in Bali Island, Indonesia. This study was conducted between July 2014 and December 2014, at three locations, namely Denpasar City, Klungkung district, and Tabanan district, at the altitudes of 35 m, 69 m and 1269 m asl. respectively. Seven species were found as new records namely Graphis modesta, Graphis immersicans, Graphis palmicola, Graphis nana, Graphis dupaxana, Graphis maritima and Graphis subradiata.